Script training treatment for adults with apraxia of speech. - Youmans, Gina; Youmans, Scott R.; Hancock, Adrienne B. (American Journal of Speech-Language Pathology, 2011)
Purpose: Outcomes of script training for individuals with apraxia of speech (AOS) and mild anomic aphasia were investigated. Script training is a functional treatment that has been successful for individuals with aphasia but has not been applied to individuals with AOS. Principles of motor learning were incorporated into training to promote long-term retention of scripts. Method: Three individuals with AOS completed script training. A multiple-baseline, acrossbehaviors design examined acquisition of clientselected scripts. Errors and speaking rates were also analyzed. Random practice and delayed feedback were incorporated into training to promote motor learning. Probes for long-term retention were elicited up to 6 months after treatment. Results: All clients successfully acquired their scripts, and probes demonstrated script retention 6 months after treatment. Errors generally decreased but remained variable even during maintenance and retention probes. Speaking rate increased for 2 clients but also remained variable. Conclusions: Script training was successful and functional for clients with AOS. Clients reported increased confidence, speaking ease, and speech naturalness. Although scripts did not become errorless, clients retained their scripts and reported using them frequently. Whether principles of motor learning may have promoted the long-term retention of scripts exhibited by participants must be determined through future research.